Issues in English Teaching - Davison, Jon; Moss, John (Issues in Teaching Series, 2000)
Issues in English Teaching invites primary and secondary teachers of English to engage in debates about key issues in subject teaching.The issues discussed include:*the increasingly centralised control of the curriculum, assessment, and pedagogy in the school teaching of English in England and Wales as a result of initiatives such as the National Literacy Strategy*new technologies which are transforming pupils' lived experience of literacy or literacies*the accelerating globalisation of English and the independence of other versions of English from English Standard English. A National Curriculum with a nationalist perspective on language, literacy and literature cannot fully accommodate English*what has become 'naturalised' and 'normalised' in English teaching, and the educational and ideological reasons for this*hierarchies that have been created in the curriculum and pedagogy, identifying who and what has been given low status, excluded or marginalised in the development of the current model of English.Issues in English Teaching will stimulate student teachers, NQTs, language and literacy co-ordinators, classroom English teachers and aspiring or practising Heads of English, to reflect on the identity or the subject, the principles and policies which, have determined practice, and those which should influence future practice.